University Educators’ Experience of Personal Learning Networks to Enhance Their Professional Knowledge - Oddone, Kay (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
This paper explores the experiences of university educators who use personal learning networks (PLNs) to enhance professional knowledge. With growing expectations to design and deliver effective online learning experiences, the PLN may offer flexible and supportive professional learning opportunities that build digital pedagogical capabilities. Previous research investigating PLNs has focused on how school teachers leverage social technologies to build these networks. However, there is limited examination of PLN use by university educators. This research is informed by the theories of networked learning and connectivism and uses a case study approach to deeply consider the experiences of five university educators from different disciplines across the globe. They share their understanding of the concept of the PLN, the influence of the COVID-19 pandemic, and how their PLN affects their digital pedagogies. The findings reveal nuanced insights of university educators’ real-life experience, shedding light on how the use of social media and other digital tools for professional learning is changing and the implications this has for the development of university educators’ understandings of digital pedagogies.